2014
DOI: 10.3109/0886022x.2014.986705
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hypertension associates with malnutrition and body composition hemodialysis patients

Abstract: Background/Aim: The prevalence of pulmonary hypertension (PH) is reported between 17 and 56% in hemodialysis (HD) patients. Pathogenesis of PH in HD patients is still unclear. Malnutrition associating impaired pulmonary function tests in HD patients previously reported. Present study aimed to investigate an association between PH and nutrition and inflammation HD patients. Patients/Methods: Total 179 HD patients (109 M, 70 F) were included. Pulmonary artery pressure (PAP) and ejection fraction (EF) percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…This is consistent with the concept that vitD itself or its metabolites do not regulate DBP production [19,38]. Previous studies also reported lower serum albumin concentrations in PAH patients [39,40] and in PAH animal models [41], suggesting that reduced albumin may be a risk factor for PAH. Following the formulas given above, calculated free 25(OH)vitD is inversely related to DBP and albumin concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the concept that vitD itself or its metabolites do not regulate DBP production [19,38]. Previous studies also reported lower serum albumin concentrations in PAH patients [39,40] and in PAH animal models [41], suggesting that reduced albumin may be a risk factor for PAH. Following the formulas given above, calculated free 25(OH)vitD is inversely related to DBP and albumin concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, AV fistula can contribute to the development of PH. Pulmonary hypertension has been shown to be associated with AV fistula by some authors [5,19] but others have shown no association [17,20]. This study too does not show any association between PH and AV fistula.…”
Section: Discussioncontrasting
confidence: 48%
“…39 Nutrition status has also been shown to be associated with disease severity. 21,40 The causes of malnutrition in PAH are multifactorial and include reduced appetite and food intake, malabsorption of nutrients, increased energy expenditure, and elevated catabolism. However, it is unclear which precise metabolic…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PAH frequently present with cachexia, the result of progressive malnutrition 39 . Nutrition status has also been shown to be associated with disease severity 21,40 . The causes of malnutrition in PAH are multifactorial and include reduced appetite and food intake, malabsorption of nutrients, increased energy expenditure, and elevated catabolism.…”
Section: Discussionmentioning
confidence: 99%